MODERN PROBLEMS OF STRATEGIC ANALYSIS AND THEIR IMPACT ON THE EFFECTIVE ACTIVITY AND MANAGEMENT OF ENTERPRISE DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction.  For the identification the current problems of strategic analysis of an enterprise, as well as their impact on the development and management of its activities in the context of rapid changes in the environment, it is necessary to form an effective system of their management.The purpose of the article. The purpose of the study is to identify the problems of modern strategic analysis and their impact on the activities of an enterprise.Methods. The article uses classical research methods, such as analysis, synthesis, comparison, which allowed to more effectively consider the current problems of strategic analysis development and propose measures for their systematic solution.Results. The main approaches to defining the concept of «strategic analysis» are considered and it is determined that strategic analysis involves identifying opportunities and threats of the external environment, strengths and weaknesses of the enterprise, determining competitive advantages and market position. It is investigated that, according to the direction of strategic analysis, the collected data is accumulated and the enterprise can make informed decisions, adapt to changes in the external environment.Conclusions. It is determined that the integration of new approaches to the implementation of strategic analysis with the help of modern analytical systems makes it possible to identify potential threats and respond to them promptly for the long-term and effective management of the enterprise in the future.
Keywords: management, development, strategy, enterprise, analysis, strategic analysis, modern problems of development, efficiency of activity, management of enterprise development.